2008
DOI: 10.1080/13880200701735577
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Antioxidant Activities of Some Plants Used as Remedies in Turkish Traditional Medicine

Abstract: The antimicrobial activities of chloroform, acetone, ethanol, and water extracts of 25 plants, mostly used as remedies against various diseases in Turkish traditional medicine, were tested against 10 pathogenic bacteria and one fungus (Candida albicans) using the disk diffusion method. Among the tested plant species, Ziziphora clinopodioides Lam (Labiatae), Thymus fallax Fisch et Mey. (Labiatae), and three Hypericum species [H. heterophyllum Vent., H. hyssopifolium Chaix. subsp. elongatum (Ledeb.) Woron var. e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
30
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 45 publications
4
30
0
2
Order By: Relevance
“…The current study showed that TAC had moderate activity against Staphylococcus strains. This finding is similar to study conducted by Unal et al (2008) who showed that T. aucheranum aerial parts chloroform extract have antibacterial activity against S. aureus. However, it has been found that T. aucheranum aerial parts chloroform extract (125 µg/mL) had higher MIC value than T. argenteum subsp.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…The current study showed that TAC had moderate activity against Staphylococcus strains. This finding is similar to study conducted by Unal et al (2008) who showed that T. aucheranum aerial parts chloroform extract have antibacterial activity against S. aureus. However, it has been found that T. aucheranum aerial parts chloroform extract (125 µg/mL) had higher MIC value than T. argenteum subsp.…”
supporting
confidence: 81%
“…However, it has been found that T. aucheranum aerial parts chloroform extract (125 µg/mL) had higher MIC value than T. argenteum subsp. argenteum aerial parts chloroform extract, reported in the present study, against S. aureus (19). Also, it is known that some flavonoids and sesquiterpene lactones have antimicrobial activity (20,21).…”
mentioning
confidence: 99%
“…Therefore, biologically active extracts and compounds from plants have commonly been studied to discover new sources [2][3][4][5][6]. Medicinal plants and herbs have been used for many years in treatments of various animal and human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…They are produced in cells by different means (Zho et al, 2006). Exogenous sources of free radicals include tobacco smoke, ionizing radiation, certain pollutants, organic solvents, and pesticides (Unal et al, 2008). ROS may cause damage on carbohydrates, proteins, lipids and DNA (Zho et al, 2006).…”
Section: Introductionmentioning
confidence: 99%